Urban air quality management in Malaysia and Thailand: A review - Norazian, Mohamed Noor; Mohd Lutfi, Zainuddin; Mohd Mustafa Al Bakri, Abdullah (Universiti Teknologi Malaysia (UTM), 2011)
2nd International Conference and Workshops on Basic and Applied Sciences (ICOWOBAS) & Regional Annual Fundamental Science Seminar (RAFSS) 2009 organized by Universiti Teknologi Malaysia, from 2nd - 4th June 2009 at The Zone Regency Hotel, Johor Bahru, Johor, Malaysia.